A holistic guide to effective prevention and treatment for kidney stones: a systematic review exploring anti-urolithiasis approaches - Anood T. Allam; Ahmed M. El-Dessouki; Riham A. El-Shiekh; Dina Abou-Hussein; Mahmoud Abdelmouti Mahmoud; Wagih H. Marcus; Hassan A. Ruby (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Urolithiasis, a disease of kidney stones, is a prevalent and recurrent condition characterized by the formation of hard mineral deposits in the urinary tract, leading to significant morbidity and a substantial healthcare burden worldwide. With recurrence rates ranging from 30 to 50% and a lifetime prevalence of 9–12% in industrialized populations, effective prevention and management strategies are crucial. Traditional approaches to urolithiasis, including pharmacological agents and surgical interventions, emphasize medical interventions and lifestyle changes; however, the persistent recurrence and impact on quality of life underscore the necessity for more comprehensive solutions. Recent advancements have focused on the potential of nutraceuticals, including herbal extracts, vitamins, and minerals, as adjuncts in the prevention and treatment of kidney stones. These agents may exert beneficial effects by inhibiting stone crystal formation, modulating urinary pH, reducing urinary calcium and oxalate excretion, enhancing diuresis, and supporting overall renal function. Moreover, these plant-based therapies may help alleviate symptoms such as pain and inflammation related to stone episodes. This systematic review synthesizes findings from 14 randomized controlled trials to assess the therapeutic impact and safety profile of various herbal interventions in patients with diagnosed kidney or ureteral stones. Thus, evidence from these recent clinical trials has increasingly supported the efficacy of single-herb and polyherbal formulations, such as Nigella sativa , Alhagi maurorum , Subap Plus, and Palasha Kshara, in modulating urinary risk factors and promoting stone expulsion. For instance, these trials demonstrated promising outcomes for several herbs: Portulaca oleracea significantly increased urinary citrate and reduced calcium, Traditional Persian Medicine-based Mofatet powder markedly reduced stone size and improved urinary parameters, Alhagi maurorum distillates and extracts showed comparable efficacy to hydrochlorothiazide in stone expulsion, and Nigella sativa performed as well as or better than tamsulosin in both pain relief and stone passage. Additional polyherbal remedies, such as Subap Plus, Palasha Kshara, and BNO 1040 extract, also yielded favourable results in improving stone clearance, easing symptoms, and potentially preventing recurrence. Notably, most studies reported good short-term tolerability and minimal adverse effects. Despite these promising findings, limitations in sample size, standardization of formulations, lack of comprehensive adverse events reporting, and need for long-term follow-up highlight the necessity for further rigorous trials.